Migratory microbiomes: the role of the gut microbiome in bird migration eco‐physiology - Pablo Capilla‐Lasheras; Alice Risely (Journal of Avian Biology)
Long‐distance bird migration is one of the most metabolically and immunologically challenging feats in the animal kingdom, with birds often needing to double their weight in a matter of days and facing increased exposure to novel pathogens. The physiological and behavioural adaptations required to survive such journeys may be facilitated by the gut microbiome, a diverse community of symbiotic microbes that produce rare nutrients, fatty acids, and immune compounds that can confer rapid physiological adaptations to changing environmental conditions. However, the causal role of the gut microbiome in regulating migration physiology remains a mystery. In this review, we synthesize current knowledge of gut microbiome composition and function during migration, outline possible mechanisms by which changes in the gut microbiome could benefit migrants, and identify future research priorities. We find that active migration is usually associated with reduced diversity of the gut microbiome and with the expansion of several study‐specific taxa. Additionally, some microbial traits have been found to correlate with host condition and fat deposits during migration. However, there remains little understanding of how changes in the gut microbiome during migration relate to most physiological parameters, the molecular mechanisms linking the gut microbiome to host physiology during migration, or the underlying ecological, dietary, and intrinsic drivers of gut microbiome changes across the migratory cycle. Our review draws from examples across non‐migratory systems to explore how gut microbiomes could adaptively regulate physiological traits relevant to migration. We highlight the need for studies that connect gut and circulating metabolites and for experimental studies that test the underlying drivers of gut microbial and metabolite dynamics in controlled settings. Given its diverse physiological demands and ubiquity, bird migration presents an excellent model system to investigate the adaptive potential of the gut microbiome in natural populations.